Visuo-spatial compound stimuli discrimination with (Gryllus pennsylvanicus) in two-choices rewarding learning tasks - André Cyr; Isaiah Morrow; Julie Morand-Ferron (Animal Cognition)
Abstract This paper proposes an experimental protocol allowing Gryllus pennsylvanicus to discriminate an A–A and A–B motif pairs of compound visual stimuli. Specifically, this study consists in an operant conditioning procedure including a dichotomous Y-maze, two different pairs of compound visual colored cues and a water reward. Results are conclusive for this visuo-spatial regularities study,(Gryllus pennsylvanicus) were able to significantly discriminate between the two compound visual patterns and learned the association with the reinforcer.